Patterns of domestication in the Ethiopian oil-seed crop noug (Guizotia abyssinica) - Dempewolf, Hannes; Tesfaye, M.; Teshome, A.; Bjorkman, Anne D.; Andrew, R.L.; Scascitelli, M.; Black, S.; Bekele, E.; Engels, Johannes M.M.; Cronk, Q.C.B.; Rieseberg, Loren H. (Wiley, 2015)
Noug (Guizotia abyssinica) is a semidomesticated oil-seed crop, which is primarily cultivated in Ethiopia. Unlike its closest crop relative, sunflower, noug has small seeds, small flowering heads, many branches, many flowering heads, and indeterminate flowering, and it shatters in the field. Here, we conducted common garden studies and microsatellite analyses of genetic variation to test whether high levels of crop–wild gene flow and/or unfavorable phenotypic correlations have hindered noug domestication. With the exception of one population, analyses of microsatellite variation failed to detect substantial recent admixture between noug and its wild progenitor. Likewise, only very weak correlations were found between seed mass and the number or size of flowering heads. Thus, noug's ‘atypical’ domestication syndrome does not seem to be a consequence of recent introgression or unfavorable phenotypic correlations. Nonetheless, our data do reveal evidence of local adaptation of noug cultivars to different precipitation regimes, as well as high levels of phenotypic plasticity, which may permit reasonable yields under diverse environmental conditions. Why noug has not been fully domesticated remains a mystery, but perhaps early farmers selected for resilience to episodic drought or untended environments rather than larger seeds. Domestication may also have been slowed by noug's outcrossing mating system